Menggugat Syirik Intelektual Bersama Nasr Hâmid Abû Zayd dan Amina Wadud - Kunawi Basyir (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2011)
The article discusses the gender issue, which has still become a global discourse within the 21st century. The discourse will always become an actual issue as it constantly emerges from women and the community’s consciousness who find strategic discrepancy and injustice in regard to the relation between men and women, which might lead to relational discrimination, subordination, stereotype, and inequality. At this point, the writer attempts to bring about the comparative analysis between two interpretation paradigms on gender issues promulgated by Nasr Hâmid Abû Zayd and Amina Wadud. Both people share a common academic apprehension when they observe the backwardness of the Muslim women in many aspects of life (as a fully human agency) caused by patriarchal tradition, gender injustice, and the problem of the minority in the Muslim world. This has subsequently caused the two authors to reconstruct the methodological paradigm of Quranic exegesis on gender issues in order to generate a just interpretation. They see the importance of having high social consciousness, which properly considers women’s existence based on humanity's sacred values. However, this view faces obstacles from other Muslim scholars as they consider Zayd and Wadud heretics and have conducted what so-called “an intellectual shirk”.